Complaints and diagnoses in homoeopathic practice - Jansen, G.R.H.J.; Koster, T.G.C. (British Homeopathic Journal, 1995)
As part of a 4-phase research project, 58 homoeopathic physicians, all members of VHAN (Dutch Association of Homoeopathic Physicians) registered for 1 week the complaints and diagnoses according to ICPC-code of the first 30 patients given exclusively homoeopathic treatment during that week. A total of 1712 patients, 36% male and 64% female, was registered. Children under 10 and adults from 30–40 years particularly sought homoeopathic treatment.